Statistical model semiquantitatively approximates arabinoxylooligosaccharides' structural diversity. (13th May 2016) - Dotsenko, Gleb; Nielsen, Michael Krogsgaard; Lange, Lene
Highlights: Statistical model approximating arabinoxylooligosaccharide structures is proposed. Structures of arabinoxylooligosaccharides from four different sources are analyzed. Predicted data are compared with experimental results. Substituted residues are not randomly distributed within wheat flour arabinoxylans. Suggested model enables substrate selection for desired oligosaccharides production. Graphical abstract: Abstract: A statistical model describing the random distribution of substituted xylopyranosyl residues in arabinoxylooligosaccharides is suggested and compared with existing experimental data. Structural diversity of arabinoxylooligosaccharides of various length, originating from different arabinoxylans (wheat flour arabinoxylan (arabinose/xylose, A / X  = 0.47); grass arabinoxylan ( A / X  = 0.24); wheat straw arabinoxylan ( A / X  = 0.15); and hydrothermally pretreated wheat straw arabinoxylan ( A / X  = 0.05)), is semiquantitatively approximated using the proposed model. The suggested approach can be applied not only for prediction and quantification of arabinoxylooligosaccharides' structural diversity, but also for estimate of yield and selection of the optimal source of arabinoxylan for production of arabinoxylooligosaccharides with desired structural features.